Rancang Bangun Sistem Informasi Monitoring Antrian pada Koperasi Setia Bhakti Wanita berbasis WEB - Putro, Muhamad Revo Dwi; Susanto, Teguh; Sutomo, Erwin (Jurnal JSIKA, 2014)
Koperasi Wanita Setia Bhakti Wanita have loan and save activities that has been devised a system of the queue to set a queue a members will do transactions. The current system of queue couldnât give the history queue to the manager HRD, the impact is difficulty in performing manager HRD to monitoring the queue. Result of monitoring queue is information what manager HRD needs and could be useful to improve transaction services.Based on the above then made monitoring system by considering the necessaries manager HRD. Monitoring system proposed is assessment of concept socketserver, the first step make client that are connected by queue server. The second step, client will record history or activities in server. The third step, recorded of history is a sequence of data couldnât be used for information. In the next step, have doing sorting a list of data will be stored and used as a source of data to make report monitoring a queue.The result of monitoring system is a report monitoring queue of comprising from reporting the real time a occurred queue, reporting the total queue, reporting the counter services (the amount queue per counter), reporting the services (total service, total service time) thatâs manager HRD used to evaluate queue system.Â Keywords: monitoring, queue, saving and loan, socketserver, client server